2010
DOI: 10.1002/adma.200902871
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous‐Processable Noncovalent Chemically Converted Graphene–Quantum Dot Composites for Flexible and Transparent Optoelectronic Films

Abstract: The preparation and optoelectronic response of flexible composites via noncovalent coupling of quantum dots to chemically converted graphene is presented. The photoinduced charge transfer is confirmed by photoconductivity measurements and the photosensitivity is improved with increasing loadings of quantum dots. This opens up a new effective route to form composites for future large‐area flexible and transparent optoelectronic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
170
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(176 citation statements)
references
References 33 publications
(34 reference statements)
5
170
1
Order By: Relevance
“…The immobilized CdSe displayed a photoconductivity about ten orders of magnitude higher than that of the pristine CdSe QD arrays. [30] It has also been found that TiO 2 deposited on RGO plates remarkably enhanced its performance in dye-sensitized solar cells [33] and in photocatalytic reactions. [32] The work function of RGO is slightly larger than that of TiO 2 , [1] which makes it effective for separation of photogenerated electron-hole pairs and transfer of the electrons to other acceptors.…”
Section: Introductionmentioning
confidence: 99%
“…The immobilized CdSe displayed a photoconductivity about ten orders of magnitude higher than that of the pristine CdSe QD arrays. [30] It has also been found that TiO 2 deposited on RGO plates remarkably enhanced its performance in dye-sensitized solar cells [33] and in photocatalytic reactions. [32] The work function of RGO is slightly larger than that of TiO 2 , [1] which makes it effective for separation of photogenerated electron-hole pairs and transfer of the electrons to other acceptors.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Herein, we report the in situ synthesis of CdSe NCs in a functionalized graphene matrix, wherein the strategy of in situ growing CdTe NCs onto a P3HT matrix has been adopted. 11 The f-GCdSe nanocomposite shows a very fast and dramatically enhanced photoresponse, which makes it an excellent electron-acceptor material for OPV devices.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The solutionbased process also has provided high feasibility of realizing flexible and large scale photovoltaic devices with costeffective fabrication. [5][6][7][8] Despite these favorable characteristics, poor charge transport and imperfect surface status of CQDs hinder high photovoltaic performance compared to the theoretical conversion efficiency. During the synthetic process, CQDs are capped by long and bulky organic ligands which enable to control the size of CQDs by preventing over-size aggregation and enhancing chemical stability.…”
mentioning
confidence: 99%